(untitled) (Swiss Medical Weekly, 2013)
Summary BACKGROUND: Femoropopliteal bruits indicate flow turbulences and increased blood flow velocity, usually caused by an atherosclerotic plaque or stenosis. No data exist on the quality of bruits as a means for quantifying the degree of stenosis. We therefore conducted a prospective observational study to investigate the sensitivity and specificity of femoropopliteal auscultation, differentiated on the basis of bruit quality, to detect and quantify clinically relevant stenoses in patients with symptomatic and asymptomatic peripheral arterial disease (PAD). METHODS: Patients with known chronic and stable PAD were recruited in the outpatient clinic. We included patients with known PAD and an ankle-brachial index (ABI) <0.90 and/or an ABI ≥0.90 with a history of lower limb revascularisation. Auscultation was performed independently by three investigators with varied clinical experience after a 10-minute period of rest. Femoropopliteal lesions were classified as follows: normal vessel wall or slight wall thickening (<20%), atherosclerotic plaque with below 50% reduction of the vessel lumen, prestenotic/intrastenotic ratio over 2.5 (<70%), over 3.5 (<99%) and complete occlusion (100%). RESULTS: Weighted Cohen’s κ coefficients for differentiated auscultation were low in all vascular regions and did not differ between investigators. Sensitivity was low in most areas with an increase after exercise. The highest sensitivity in detecting relevant (>50%) stenosis was found in the common femoral artery (86%). CONCLUSION: Vascular auscultation is known to be of great use in routine clinical practice in recognising arterial abnormalities. Diagnosis of PAD is based on various diagnostic tools (pulse palpation, ABI measurement) and auscultation can localise relevant stenosis. However, auscultation alone is of limited sensitivity and specificity in grading stenosis in femoropopliteal arteries. Where PAD is clinically suspected further diagnostic tools, especially colour-coded duplex ultrasound, should be employed to quantify the underlying lesion.